2015
DOI: 10.1109/tdei.2015.7116319
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical characteristics of high-κ Sm2TiO5gate dielectrics for InGaZnO thin-film transistors

Abstract: In this study, we developed an amorphous indium-gallium-zinc oxide (-IGZO) thinfilm transistor (TFT) incorporating high- Sm 2 TiO 5 gate dielectrics. The high- Sm 2 TiO 5 -IGZO TFT after annealing at 400°C exhibited very good electrical characteristics, such as a high I on/off ratio of 5.27×10 7 , a high field-effect mobility of 27.8 cm 2 /V-sec, a low threshold voltage of 0.2 V, and a low subthreshold swing of 136 mV/decade. These results are probably due to the incorporation of Ti into the Sm 2 O 3 film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[29][30][31] Several studies have reported that IGZO TFTs with a ZrO 2 gate dielectric might have good performance. 32,33) In addition, it has been reported that the suitable incorporation of SiO 2 with high-κ materials could modulate the dielectric constant, reduce the density of bulk defects, smooth the film surface, and improve the trap density of channel=dielectric interfaces. [34][35][36][37] In this work, to improve the quality of the ZrO 2 gate dielectric, Zr x Si 1−x O 2 films obtained from the room-temperature co-sputtering of ZrO 2 and SiO 2 targets are proposed for the gate dielectric of IGZO TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Several studies have reported that IGZO TFTs with a ZrO 2 gate dielectric might have good performance. 32,33) In addition, it has been reported that the suitable incorporation of SiO 2 with high-κ materials could modulate the dielectric constant, reduce the density of bulk defects, smooth the film surface, and improve the trap density of channel=dielectric interfaces. [34][35][36][37] In this work, to improve the quality of the ZrO 2 gate dielectric, Zr x Si 1−x O 2 films obtained from the room-temperature co-sputtering of ZrO 2 and SiO 2 targets are proposed for the gate dielectric of IGZO TFTs.…”
Section: Introductionmentioning
confidence: 99%